Technical note: Implementation of prescribed (OFFLEM), calculated (ONLEM), and pseudo-emissions (TNUDGE) of chemical species in the Modular Earth Submodel System (MESSy) - A. Kerkweg; R. Sander; H. Tost; P. Jöckel (Atmospheric Chemistry and Physics, 2006)
We present the submodels OFFLEM, ONLEM, and TNUDGE for the Modular Earth Submodel System (MESSy). Prescribed emissions from input files are handled by OFFLEM. ONLEM deals with online-calculated emissions, i.e., emissions that are calculated during the simulation. The submodel TNUDGE uses the "tracer nudging" technique for pseudo-sources and -sinks. For species with highly uncertain emission fluxes and/or with sufficiently long lifetimes, e.g., CH4, it is common to create such pseudo-fluxes by prescribing the observed mixing ratio of the species at a given boundary (e.g., the mixing ratio of methane at the surface, or the ozone mixing ratio at the tropopause). All three submodels substantially simplify the inclusion of emissions into a model. Specific emissions can easily be switched on or off. New prescribed emissions can be included without rewriting any code. New online emissions only require one additional subroutine containing the new parameterization. A major advantage is that input fields at arbitrary resolution can be used. The problem of incompatible grids between emission data and model is overcome by utilizing the MESSy data import interface. To further simplify the creation of new offline emission data, the preprocessing program EDGAR2NC is provided. EDGAR2NC transforms files from the EDGAR format into the netCDF format which is required by OFFLEM. The presented routines are a part of the community modeling project MESSy and can be made available for use to the atmospheric modeling community.